RNA binding proteins in osteoarthritis - Yi, Qian; Deng, Zhenhan; Yue, Jiaji; He, Jinglong; Xiong, Jianyi; Sun, Wei; Sun, Weichao (Frontiers in Cell and Developmental Biology, 2022)
Osteoarthritis (OA) is a common chronic degenerative joint disease worldwide. The pathological features of OA are the erosion of articular cartilage, subchondral bone sclerosis, synovitis and metabolic disorder. Its progression characterized by aberrant expression of genes involved in inflammation, proliferation, and metabolism of chondrocytes. Effective therapeutic strategies are limited, as mechanisms underlying OA pathophysiology remain unclear. Significant research efforts are ongoing to elucidate the complex molecular mechanisms underlying OA focused on gene transcription. However, post-transcriptional alterations also play significant function in inflammation and metabolic changes related diseases. RNA-binding proteins (RBPs) have been recognized as important regulators in post-transcriptional regulation. RBPs regulate RNA subcellular localization, stability and translational efficiency by binding to their target mRNAs, thereby controlling their protein expression. But their role in OA is less clear. Identifying RBPs in OA is of great importance to better understand OA pathophysiology and to figure out potential targets for OA treatment. Hence, in this manuscript, we summarize the recent knowledge on the role of dysregulated RBPs in OA and hope it will provide new insight for OA study and targeted treatment.